(untitled) (Web of Teachers: Inderscience Research, 2025)
English for Specific Purposes (ESP) is a specialized area within English language teaching. It focuses on giving learners the English language skills they need to communicate effectively in their specific professional, academic, or job-related situations. This article looks at the main ideas, teaching methods, and challenges involved in teaching ESP. It stresses how important it is to analyze learners’ needs, use authentic materials, and make teaching learner-centered when designing ESP courses. The article also talks about the best ways to teach ESP and what the future holds, including the growing role of technology and the increasing need for ESP in today’s interconnected world.